Adverse drug reactions in geriatric patient with chronic asthma - T, Dixon; Zachariah, Seeba; M, Molly; R. C, Vijaya (Indian Journal of Pharmacy Practice)
A 70 year old male with chronic asthma was presented to the hospital pharmacy in a primary health center in Kannur, India. The patient was unable to walk without help was tired and was experiencing wheezing with his breathing. He had severe itching, bruises, thinned skin, and gastrointestinal bleeding as observed by the pharmacist. He was diagnosed by his physician as having uncontrolled asthma, gastrointestinal bleeding and Stevens-Johnson syndrome. The patient had taken Salbutamol, Diclofenac and Betamethasone for three years without valid prescription. It was a case of problem due to self medication by the patient and community pharmacist dispensinging the medication without a prescription.
Keywords: Self Medication; asthma; salbutamol; pharmacist